The light in the Old English Rhyming Poem, lines 1–2 - Soper, H (Oxford University Press, 2019)
The opening lines of the Exeter Book’s Rhyming Poem (RP) reflect the generally enigmatic and imagistic approach of this unusual piece of Old English verse, which sustains end-rhyme alongside its alliterative metre throughout. In doing so, the text is unique in the surviving corpus of Old English poetry, although shorter rhyming passages can also be found in longer poems such as Cynewulf’s Elene (1236–50) and Christ II (591–6).